1999
DOI: 10.1152/ajpgi.1999.276.3.g687
|View full text |Cite
|
Sign up to set email alerts
|

Factors mediating the hemodynamic effects of tumor necrosis factor-α in portal hypertensive rats

Abstract: Nitric oxide, prostacyclin, and glucagon have been implicated in promoting the hyperdynamic circulatory state of portal hypertension. Recent evidence also indicates that increased tumor necrosis factor-α (TNF-α) production is involved in the pathogenesis of this hemodynamic abnormality. This study was aimed at investigating in rats with portal vein stenosis (PVS) the effects on splanchnic hemodynamics of blocking circulating TNF-α and the factors mediating the vascular action of this cytokine in this setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 23 publications
4
49
0
3
Order By: Relevance
“…In addition, TNFa is known to activate MMP (Polavarapu et al, 2005;Thomson et al, 2012), which is critical in aneurysm pathology. Risk factors associated with aneurysm development have been associated with TNFa induction (Jayaraman et al, 2008), including hypertension (Munoz et al, 1999) Sun et al, 2007;Wright et al, 2007). In a study by Jayaraman et al (2005), the expression of TNFa and its proapoptotic downstream target FAS were increased in IA, indicating that TNFa has a proapoptotic and pro-inflammatory action in the wall of aneurysms.…”
Section: Cytokines Growth Factors and Other Mediatorsmentioning
confidence: 99%
“…In addition, TNFa is known to activate MMP (Polavarapu et al, 2005;Thomson et al, 2012), which is critical in aneurysm pathology. Risk factors associated with aneurysm development have been associated with TNFa induction (Jayaraman et al, 2008), including hypertension (Munoz et al, 1999) Sun et al, 2007;Wright et al, 2007). In a study by Jayaraman et al (2005), the expression of TNFa and its proapoptotic downstream target FAS were increased in IA, indicating that TNFa has a proapoptotic and pro-inflammatory action in the wall of aneurysms.…”
Section: Cytokines Growth Factors and Other Mediatorsmentioning
confidence: 99%
“…Patients and animal models with portal hypertension had an elevated TNF-α level which stimulated release of nitric oxide (NO) and prostacyclin, important mediators of a hyperdynamic circulation [148] . For example, in one study, 96 healthy rats were injected with either anti-TNF-α polyclonal antibodies or placebo before surgically creating portal vein stenosis (PVS) to induce portal hypertension and 4 d after in the short-term inhibition group and 1, 4, 7 and 10 d after PVS in the long term-inhibition group.…”
Section: Angiogenesismentioning
confidence: 99%
“…In another study, iNOS and cNOS levels were also higher in gastric mucosa of patients with PHG than in controls [153] , and were significantly higher in patients with severe PHG as compared to patients with mild or no PHG [154] . Nitrous oxide may underlie the gastric vascular dilation [152] , and hyperdynamic circulation in PHG [148] . However, Lee et al [155] reported administration of aminoguanidine, an iNOS inhibitor, successfully corrected the hyperdynamic circulation without affecting PHG, suggesting that iNOS and NO are important in the hyperdynamic circulation in portal hypertension, but play a limited role in PHG development.…”
Section: Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Hecho que no hace sino enfatizar la relevancia del aumento de flujo esplácnico en el desarrollo de la colateralización portosistémica. Consecuencias similares se logran inhibiendo el TNF-alfa circulante, citoquina proinflamatoria cuya concentración sérica está aumentada en la hipertensión portal, y que estimula la actividad de la eONS (29). Más recientemente, se ha demostrado que el bloqueo de mediadores específicos de la angiogé-nesis, como el VEGF, también atenúa la colateralización portosistémica (44,51).…”
unclassified